PENGARUH PENERAPAN SISTEM AKUNTANSI INSTANSI TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI KASUS PADA KANTOR BALAI WILAYAH SUNGAI MALUKU) - Persulessy, Grace; Giovani Manuputty, Gino; Lekatompessy, Selvi (Widya Warta, 2018)
This study aimed to determine the effect of the application of Institution Accounting System to the quality of Financial Statements. The population selected in this study were employees who worked at the Moluccas River Region Hall; they were 169 people. The samples in this study were the financial, program and data, and the employment head of 40 people. Data collection methods used by researchers were questionnaires and documentation, while data analysis was done with simple linear regression. The result of the research showed that Institution Accounting System had positive and significant effect on the quality of financial report.